Expression of CEA, CA125 and P16INK4A in the Normal Breast, Fibroadenoma and Invasive Adenocarcinomas of the Breast - Victor Ekundina; Oladele Ayowole; Praise Awe; Temidayo Adeniyi; Adah Emmanuel-Omah; Duchess Eigbefoh; Adegoke Aremu; Adegoke Aremu (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The incidence rate of breast cancer is higher in developed countries and it varies greatly with race and ethnicity. The p16INK4A, a tumor suppressor gene, CA125, a gene involved in the arrest of the cell cycle and CEA, a cellular adhesion molecule are markers that have been expressed in breast cancer cases in previous studies, however this study was aimed at studying the various expression patterns of these markers at different stages of breast cancer starting from the normal breast, fibroadenoma down to the invasive adenocarcinoma of the breast. Sample and method. A total of 65 breast tissue blocks which included 15 normal breast tissue blocks, 25 fibroadenoma tissue blocks, and 25 breast tissue blocks with invasive adenocarcinoma diagnosis was provided by pathological archives of Obafemi Awolowo University Teaching Hospital Complex. These blocks were then used to make immunohistochemical stained sections which were analyzed using a digital camera and a LEICA research microscope after which photomicrographs were taken. Results. In p16, a positivity rate of 13% was shown in normal cases, 84% in fibroadenoma cases with moderate cytoplasm and nuclear staining and 92% in invasive adenocarcinoma cases with various degrees of positivity thereby indicating an overexpression in the invasive adenocarcinoma of the breast. In CA125, the normal cases showed a positivity rate of 60%, the fibroadenoma cases showed a positivity rate of 72% while the invasive adenocarcinoma cases had a positivity rate of 84% indicating a pattern of upregulation from the normal breast cases down to the invasive adenocarcinoma of the breast with cytoplasmic staining. CEA was also found to be overexpressed in the cases of invasive adenocarcinoma of the breast while showing a membranous staining with a positivity rate of 76% and a positivity rate of 60% in fibroadenoma cases while no positive reaction was observed in any of the normal breast cases thereby having a positivity rate of 0%. Although p16, CA125 and CEA appeared to be overexpressed in invasive adenocarcinoma of the breast, p16 was found to be the most reliable of them all. Conclusion. After carrying out this investigation, it was concluded that using these markers (p16, CA125 and CEA) singlehandedly to monitor the progression of breast cancer at the normal breast stage, fibroadenoma and invasive adenocarcinoma of the breast will not produce very reliable and specific results as compared to using all the markers at once. It is thereby advisable to use these three markers at the same time in order to reduce the chances of false positive or false negative results.